Exploration of the preventive effect of S. lessoniana liver oil on cardiac markers, hematological patterns and lysosomal hydrolases in isoproterenol-induced myocardial infarction in wistar rats: a novel report. Issue 68 (5th July 2016) - Moovendhan, Meivelu; Seedevi, Palaniappan; Shanmugam, Annaian; Vairamani, Shanmugam
Abstract : The purpose of this study was to explore the in vivo cardioprotective potency of liver (digestive gland) oil from S. lessoniana on isoproterenol induced myocardial infracted wistar rats. Abstract : The purpose of this study was to explore the in vivo cardioprotective potency of liver (digestive gland) oil from S. lessoniana on isoproterenol induced myocardial infracted wistar rats. Rats received IPH for 2 successive days (85 mg kg −1 body weight) at 24 h intervals to induce myocardial infarction at the end of the experiment. S. lessoniana liver oil was served orally at a dose of 0.05 mL per day for 45 days, then the serum and heart tissue were analysed for CK and LDH enzyme activity, then haematological, lipid profile changes was examined in the blood, histopathological examination was carried in heart tissue and the activity of β-d -glucuronidase, β-d -acetylglucosaminidase, acid phosphatase and cathepsin-D in the serum lysosomal heart fraction. The results of the present study suggested that the pre-treated animals with squid liver oil prevented isoproterenol-induced haematological changes and heart weight increases. Lysosomal membrane integrity was well protected in rats pre-treated with squid liver oil, as indicated by significantly lowered activities of lysosomal hydrolases in the serum and associated increase in their activity in the lysosomal fraction of the heart. The histopathological examination further confirmed that the cardioprotective potency of squid liver oil.